Correction: Badri et al. An Efficient and Secure Model Using Adaptive Optimal Deep Learning for Task Scheduling in Cloud Computing. Electronics 2023, 12, 1441 - Badri, Sahar; Alghazzawi, Daniyal M.; Hasan, Syed Humaid; Alfayez, Fayez; Hasan, Syed Hamid; Rahman, Monawar; Bhatia, Surbhi (Electronics (Basel), 2025)
In the original publication [...]